Síntese, caracterização e estudo fotofísico de filmes de poliestireno sulfonado dopados com Nd3+ - Cristovan, Fernando Henrique (2004)
The new materials sciences are academic important due to their rich physic-chemistry phenomena to the development of new technological equipments. In the case of Rare-Earths (TR), these applications include the production of optical components, glasses, fluorescents lights, nuclear energy equipment’s and others. The lanthanides are of high interest, once their optical properties is not affected by the host material, and by this way the investigation of the TR ions consent a study of the electronic properties of this materials, even on solid state. In the present work, was prepared sulfonated polystyrene (PSS) films doped with Neodymium ions (Ndªª), using a easy and economic synthesis route. Was made too a chemistry characterization and the photo-physics study of the films. With the aim of improve the process, was made an optimization using chemometrics methods. These methods indicates the best experimental condition to the ﬁlms acquisition and the maximum percentage of incorporation of Nd3+, about 13.52%. The spectroscopic data presents similar results to the literature. The UV-Vis-IR spectrum presents characteristic electronic transition of the Nd3+, and the 4I9/2 —> 4F5/2 + 2H9/2 transition at 800nm was the more intense. The IR spectrum presents an enlargement as a possible result of Nd3+ coordination with the polymer. The IR emission of the Nd-PSS films presents similar to the Neodymium emission in others glasses hosts, where was observed the emission on 1061 nm (4F3/2 —> 4I11/2).